حلِّ مختلف الحدیث:صاحبِ بزل المجہودکا اسلوب و منہج - مفتی محمد ہارون; ڈاکٹر محمد شہباز منج (FIKR-O NAZAR فکر ونظر, 2014)
‘Ilm Mukhtalaf al-hadith, the science of harmonizing the contradictory hadith narrations, is of vital importance in interpreting the hadith texts. With this perspective, the present article studies a multi-voluminous commentary of a well known classical hadith corps Sunan Abi Dawud, penned by an Indian scholar Khalil Ahmad Saharanpuri (d. 1927 AD), called Badhl al-Majhud fi Hall Sunan Abi Dawud. This study finds that Saharanpuri integrates both the received classical methods of jurists (usuliyyin) and traditionists (muhaddithin) for interpreting and harmonizing the hadith texts. It argues that although Saharanpuri belongs to the traditional camp, he views the existed tradition with critical lens. Equally being aware of the challenges of modernity, he engages himself for resolving its issues in a logical way.